H3K4me3-Mediated Upregulation of LncRNA-HEIPP in Preeclampsia Placenta Affects Invasion of Trophoblast Cells - Sun, Ningxia; Chen, Huaiyan; Ma, Yan; Pang, Wenjuan; Wang, Xiang; Zhang, Qing; Gao, Lu; Li, Wen (Frontiers in Genetics, 2020)
Preeclampsia (PE) is a pregnancy-related disease defined as onset of hypertension and proteinuria after the 20th week of pregnancy, which causes most maternal and perinatal morbidity and mortality. Although placental dysfunction is considered as the main cause of PE, the exact pathogenesis of PE is not yet fully understood. Long noncoding RNAs (lncRNAs) are implicated in a broad range of physiological and pathological processes, including the occurrence of PE. In this study, we investigated the expression and functions of HIF-1alpha pathway related lncRNA-HEIPP (High expres-sion in preeclampsia placenta) in the pathogenesis of preeclampsia. The expression of lncRNA-HEIPP in the placenta from women undergone preeclampsia were screened by lncRNA microarray and then verified using real-time PCR. Then the methylation profile of the lncRNA-HEIPP promoter and the enrichment of H3K4me3 binding was assessed by bisulphite pyrosequencing and ChIP-qPCR assay, respective-ly. It was found that the level of lncRNA-HEIPP in the preeclampsia placenta was sig-nificantly higher than that in normal placenta, and was increased in HTR-8/SVneo human trophoblast cells upon hypoxia treatment. Moreover, we reported that H3K4me3 manifested significantly higher promoter occupancy on lncRNA-HEIPP promoter in HTR-8/SVneo cells upon hypoxia treatment, and found that the down-regulation of lncRNA-HEIPP promoted trophoblast invasion. Our findings suggested that the hypoxia-induced expression of lncRNA-HEIPP mediated by H3K4me3 modifi-cation in trophoblast may contribute to the pathogenesis of preeclampsia.